Participant outcomes of restorative justice conferencing within a higher education student disciplinary context - Wichmann, Brooke Elizabeth, author; Cavanagh, Tom, advisor; Chesson, Craig, committee member; Vigil, Patricia, committee member; Donovan, Jody, committee member (Colorado State University. Libraries, 2025)
The focus of this dissertation was to understand the experiences of participants who engaged in restorative justice conferencing as part of a university's student conduct process. Student misconduct has long been a challenge within higher education, and some see restorative justice as an effective means of addressing student violations of university rules and norms. While restorative justice has been associated with positive outcomes for participants in criminal justice and K-12 educational settings, little research has been done on restorative justice within higher education. With more colleges and universities interested in incorporating restorative justice into their student conduct process, it is important to understand the experiences of participants who engage in restorative justice processes in these settings. As part of this dissertation, a non-experimental quantitative study was conducted with victims, student offenders, and community members who participated in a restorative justice conference as part of Colorado State University's student conduct process. Participants were administered pre and post-conference surveys with quantitative questions designed to obtain information about their attitudes, perspectives, experiences, and motivations. Quantitative descriptive analysis was used to investigate the frequency and variation of their scores and connections were explored between participant responses and the restorative justice theoretical paradigm, empirical findings of restorative justice research, and contemporary student conduct standards. The findings of this study suggest that it is possible for campus restorative justice programs to foster positive experiences for participants, follow contemporary student conduct standards, and be aligned with restorative justice theory. The dissertation concludes with recommendations for future research that are presented along with implications for practice to help colleges and universities operate effective restorative justice programs.
Keywords: higher education; student conduct; restorative justice; conferencing